Impact of ITS-Based Sequencing on Antifungal Treatment of Patients with Suspected Invasive Fungal Infections - Sara Guenter; Gregor Gorkiewicz; Bettina Halwachs; Karl Kashofer; Andrea Thueringer; Phillip Wurm; Ines Zollner-Schwetz; Thomas Valentin; Juergen Prattes; Stefanie Wunsch; Elisabeth Ullrich; Christoph Zurl; et al. (Journal of Fungi, 2020)
Molecular techniques including the sequencing of fungal-specific DNA targets are increasingly used in the diagnosis of suspected invasive fungal infections. In contrast to established biomarkers like galactomannan or 1-3-β-d-glucan, the clinical impact of these methods remains unknown. We retrospectively investigated the impact of ITS1-sequencing on antifungal treatment strategies in 71 patients (81 samples) with suspected invasive fungal infections. ITS-sequencing either confirmed already ongoing antifungal therapy (19/71 patients, 27%), led to a change in antifungal therapy (11/71, 15%) or supported the decision to withhold antifungal treatment (34/71, 48%) (in seven of 71 patients, ITS-sequencing results were obtained postmortem). ITS-sequencing results led to a change in antifungal therapy in a relevant proportion of patients, while it confirmed therapeutic strategies in the majority. Therefore, ITS-sequencing was a useful adjunct to other fungal diagnostic measures in our cohort.